Linguistic representation of gender from essentialist to poststructuralist perspective in the Cholistan trilogy: a feminist critical discourse analysis (Journal of Humanities, Social and Management Sciences (JHSMS-Asia), 2022)
The identities of gender normative get deconstructed and reconstructed with alternate possibilities of self-constitution. This phenomenon is rendered more complex with its intersection with other factors of identities like race/ethnicity, social class, geography etc. The linguistic representation of these complex variegated aspects of gender from its essentialist to poststructuralist perspectives was analysed in Staples’s Cholistan trilogy which consists of three novels Shabanu (1989), Haveli (1993) and The House of Djinn (2008). An eclectic approach of a theoretical framework consisting of Lazar’s (2005; 2007; 2014) Feminist Critical Discourse Analysis (FCDA), Butler’s (1990) gender performativity and Foucault’s (1980) subjectivity theory was adopted. Halliday’s (1985) approach to transitivity analysis was used for analysing the transitivity processes in the performances of gendered subjects described in the verbal phrases of the clauses in the text. Various kinds of constructions of gender identities were revealed in the study like biological determination of gender, the social construction of gender, the configuration of gender, gender stereotypes, deconstruction of gender normativity and reconstruction of gender identities with possible alternate performances. The study recommends the textual representation of gender in a way that help deconstructs gender normative and reconstruct gender identity with alternate possibilities.